Chemical control of signalgrass for establishing Tanzania-grass (Acta Scientiarum. Animal Sciences, 2020)
Herbicides have been used to control Brachiaria grass in pastures established or in formation given their practicality, however their efficiency is questionable due to the lack of specific graminicides for different forage species. Therefore, the goal of this study was to evaluate the efficiency of glyphosate and fluazifop-p-butyl in the control of Brachiaria decumbens (signalgrass) and the intoxication levels of Panicum maximum cv. Tanzania (Tanzania quinea grass) in pasture establishment. The experiments were designed in randomized blocks, in a 2 Ã— 5 Ã— 4 factorial arrangement of two herbicides (fluazifop-p-butyl and glyphosate), five doses equivalent to the commercial dosage of each herbicide (0.25; 0.50; 1.00; 1.50; 200), and four evaluation times after herbicide application (15, 21, 30 and 45 days). There was interaction between doses and evaluation times. The dose 1.5 L ha-1 fluazifop-p-butyl provides efficient control of signalgrass, however, leads to high intoxication in Tanzania guinea grass. Glyphosate is efficient in the control of signalgrass even at the lowest dose (90 g ha-1), however, it causes high intoxication in Tanzania guinea grass, preventing its use in developing pastures. It can be concluded that fluazifop-p-butyl and glyphosate herbicides are not recommended for the control of B. decumbens, cv. Basilisk in developing pastures of Tanzania guinea grass.